PERLINDUNGAN HUKUM BAGI TRANSGENDER DITINJAU DARI PERSPEKTIF HAK ASASI MANUSIA - Wati, Dyan Mardika; Husodo, Jadmiko Anom (Department of the Constitutional Law, Faculty of Law Universitas Sebelas Maret, 2018)
This research aims to find out more about the importance of providing protection to transgender as Indonesian citizens. Learn more about legal protection of transgender and how it is implemented. The research method used is a normative or legal research that is prescriptive with approach of Legal Approach and Case Approach which uses primary legal material that is legislation and secondary legal material is books, journals and other sources that are still relevant to this research. The results of the research can be seen that the legal protection as citizens of Indonesia from discrimination is already running but not maximized, this is because transgender at this time still get unpleasant behavior. Constraints to the transgender protection are the absence of a firm stance from the government in addressing the issue of protection to transgender, the absence of a legal regulation made specifically for transgender conditions and indifferent to transgender society.